Sosialisasi Pendidikan untuk Meningkatkan Peran Orang Tua dalam Mendukung Pendidikan Anak di Desa Tanjung Labu - Fitriya Fitriya; Amala Nurjanah; Danu Ardiansyah; Refi Arzeti; Ridho Alfaridzi; Sevira Violita; Ilvina Arfiza; Widya Ningsih; Tengku Islamilzza Najib; Fitria Anggraini; Fitri Yanti; Nurzaidah Putri Dalimunthe; Ratno Purnama Sari (Jurnal Pengabdian Masyarakat Waradin, 2025)
Education plays an important role in shaping children's futures, and parental support is one of the key factors in ensuring educational success. This article aims to discuss the importance of educational socialization as an effort to raise awareness and enhance parents' roles in supporting their children's education, particularly within the community of Tanjung Labu Village. Through collaboration between SD Negeri 1 Lepar and students from Muhammadiyah University of Bangka Belitung conducting community service programs in Tanjung Labu, it is hoped that parents will be increasingly motivated to actively participate in their children's education. This article also proposes relevant strategies and socialization programs to strengthen awareness of the importance of parental involvement in supporting children's continuous education. The socialization initiative recommends implementing sustainable programs to further optimize parental support for their children's education.